2015
DOI: 10.1093/ndt/gfv065
|View full text |Cite
|
Sign up to set email alerts
|

High interpatient variability in response to mycophenolic acid maintenance therapy in patients with ANCA-associated vasculitis

Abstract: Due to the highly variable response to maintenance therapy with MPA, PD drug monitoring is a new tool for detecting inadequate immunosuppression in AASV patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Infectious complications are the leading cause of death during the first year after disease onset [8][9][10]. Efforts have been made to reduce the immunosuppressive burden either through reducing cumulative immunosuppressive dose, performing therapeutic drug monitoring or through replacing commonly used medication by more disease-specific, less toxic agents [13,[19][20][21]. We aimed to investigate the impact of GC maintenance dose and duration on AAV patient outcomes with an emphasis on infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious complications are the leading cause of death during the first year after disease onset [8][9][10]. Efforts have been made to reduce the immunosuppressive burden either through reducing cumulative immunosuppressive dose, performing therapeutic drug monitoring or through replacing commonly used medication by more disease-specific, less toxic agents [13,[19][20][21]. We aimed to investigate the impact of GC maintenance dose and duration on AAV patient outcomes with an emphasis on infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration range was reduced by 10-fold in subsequent experiments due to the potent inhibitory effects of MPA on ECFC in vitro . This raises concern that MPA at current patient therapeutic doses may possess potential vascular toxicity especially with the notable narrow therapeutic index of MPA and large intra- and inter-individual variation in both MPA plasma concentrations and levels of IMPDH activity [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] DMARDs, including mycophenolic acid, were administered for 2 months, but the wound healing response was very poor. Although mycophenolic acid might play a role in the treatment of anti-neutrophil cytoplasm antibody-associated systemic vasculitis, [ 6 ] we consider the mycophenolic acid therapy in our patient to be unsuccessful. The wounds continued to heal without mycophenolic acid post third dose of omalizumab, which indicated that the patient did not respond to mycophenolic acid.…”
Section: Discussionmentioning
confidence: 92%